Non-economic elements in the construction of the soccer market: myte of the hero and flexibilization in legislation - Jardim, Maria Chaves; Varela, Thierry Gabriel (Laboratório Editorial Faculdade de Ciências e Letras, 2019)
The article deals with the social construction of the soccer market in Brazil, seeking to identify non-economic elements that help to support this marketInspired by economic sociology, he argues that cultural variables (myth of the player as a hero) and social variables (flexibility in legislation), help to explain the high economic movement of this market, especially after the 2000s. It had as methodology the research of field in the Railway of Araraquara and research in the internet.